Analysis of the Association Between Running Distances and Match Outcomes in Professional Football During the 2022–2023 Season - HAFIZ, Seyid Ahmet; YANAR, Senol; COBAN, Cansu (Acta Scientiae et Intellectus, 2025)
In this study, it was aimed to evaluate the relationship between the total and different speed running distances travelled by professional football players during the competition and the results of the competition. Twenty-nine official competitions of a team competing in the Turkish professional football third division were evaluated. High intensity running, sprint and total running distances were evaluated from the running distances travelled in the competition, while the competition results were obtained from the official website of TFF. The distances travelled in the competitions were recorded through GPS technologies. Pearson correlation analysis was applied to evaluate the relationship between running distances travelled by football players in competitions and competition results. Our study revealed that the running distances travelled in the competition may be helpful in determining the level of players and the needs of football, but it is not sufficient alone to determine the result of the competition (p>0.05). We believe that these results will support to future studies on the similar subject.